Study on launching technique of a 98 kJ electric gun for hypervelocity impact experiments. (December 2018) - Song, Zhenfei; Mo, Jianjun; Zhao, Jianheng; Tan, Fuli; Yuan, Hong
Highlights: Establishing a 98 kJ electric gun for performing hypervelocity impact tests. Developing launching techniques for maintaining the completeness and flatness of a launched flyer plate. Developing the electric gun apparatus as a versatile tool for dynamic high-pressure experiments. Plasma shock waves have been detected during circuit discharging process using developed instantaneous momentum measuring technique. Abstract: An electric gun with the maximum stored energy of 98 kJ is established for hypervelocity impact (HVI) ballistic tests on Whipple shields of space debris. The status of a launched flyer, being crucial of HVI ballistic tests, and the influence of the plasma following the flyer has been experimentally evaluated. By improving the fabrication technique of bridge-foil laminates, a flyer plate is driven by evenly distributed foil expansion and plasma expansion. A 10 mm-diameter and 0.2 mm-thick mylar flyer is launched up to ∼12 km/s and a 18 mm-diameter and 1.0 mm-thick mylar plate up to ∼4.5 km/s. Both the flyers maintain their completeness. The circuit of the electric gun is also reformed to eliminate the formation of plasma shock waves with the amplitude as high as 20 GPa. Such an electric gun has been applied not only for HVI ballistic tests on Whipple shields, but also as a versatile tool for dynamic high-pressure experiments.